Comprehensive care and HIV prophylaxis after sexual assault in rural South Africa: the Refentse intervention study. (13th March 2009) - Kim, Julia C; Askew, Ian; Muvhango, Lufuno; Dwane, Ntabozuko; Abramsky, Tanya; Jan, Stephen; Ntlemo, Ennica; Chege, Jane; Watts, Charlotte
Abstract : Problem Although international guidelines specify the central role of the health sector in providing comprehensive care, including HIV post-exposure prophylaxis (PEP), after sexual assault, in both industrialised and developing countries there are many challenges to providing timely and comprehensive services. Design A nurse driven model of post-rape care was integrated into existing hospital services; the before and after study design evaluated impacts on quality of care, reviewing 334 hospital charts and conducting interviews with 16 service providers and 109 patients. Setting 450 bed district hospital in rural South Africa. Key measures for improvement Quality of care after rape (forensic history and examination, provision of emergency contraception, prophylaxis for sexually transmitted infections, referrals); provision of HIV counselling and testing and provision and completion of full 28 day course of PEP; and service utilisation (number of service providers seen on first visit and number of rape cases presenting to hospital per month). Strategies for change After completing baseline research, we introduced a five part intervention model, consisting of a sexual violence advisory committee, hospital rape management policy, training workshop for service providers, designated examining room, and community awareness campaigns. Effect of change Existing services were fragmented and of poor quality. After the intervention, there were considerable improvements in clinical history and examination, pregnancy testing, emergency contraception, prophylaxis for sexually transmitted infections; HIV counselling and testing, PEP, trauma counselling, and referrals. Completion of the 28 day course of PEP drugs increased from 20% to 58%. Lessons learnt It is possible to improve the quality of care after sexual assault, including HIV prophylaxis, within a rural South African hospital at modest cost, using existing staff. With additional training, nurses can become the primary providers of this care.